Validation of Sport Anxiety Scale-2 (SAS-2) among Polish athletes and the relationship between anxiety and goal orientation in sport - Tomczak, M.; Kleka, P.; Walczak, A.; Bojkowski, L.; Gracz, J.; Walczak, M. (Scientific Reports, 2022)
This study aims to assess the validity and reliability of the Polish version of the Sport Anxiety Scale-2, as well as to determine the relationship between anxiety and goal orientation among high-performance and recreational athletes. A total of 519 athletes aged M = 22.83 (SD = 4.92) participated in the study, including 266 males and 253 females. 242 athletes trained professionally and 277 recreationally. The Sport Anxiety Scale-2 (SAS-2) was used to assess anxiety levels, while the Task and Ego Orientation in Sport Questionnaire (TEOSQ) and the Perception of Success Questionnaire (POSQ) enabled to assess athletes` goal orientation. Confirmatory factor analysis showed a good fit of the model to the data for the Polish version of the Sport Anxiety Scale-2 (CFI = 0.945, RMSEA = 0.072). The models obtained during analysis of high-performance and recreational athletes, women and men, also presented a satisfactory fit to the data (CFI 0.932-0.946). The configural, metric, scalar and strict measurement invariances were demonstrated for high-performance and recreational athletes as well as among women and men. High internal consistency coefficients (alpha 0.81-0.91) and a high test-retest reliability indexes were reported (ICC 0.74-0.87). Women presented higher level of competitive anxiety than men. A positive relationship between competitive anxiety and athletes` ego orientation was also presented. This relationship concerned particularly women practicing sport recreationally.